Punishment for Being Late to School by Reading the Al-Qur’an from the Perspective of an Ismuba Teacher at SMK Muhammadiyah 3 Wates - Andini, Rahmah Ayu; Roviana, Sri; Wicaksana, Apri Wulandari (Journal of Islamic Education and Ethics, 2024)
This research aims to find out the background of reading the Qur’an as a condition for obtaining permission to attend lessons when students are late for school. Is it true that the Al-Qur'an is used as punishment? Remember that if it is used as a punishment, it will give each student a bad perception of the Al-Qur’an. Data was obtained at SMK Muhammadiyah 3 Wates with sources from Ismuba teachers (Al-Islam Kemuhammadiyahan and Arabic) consisting of Heru as deputy head of Ismuba at SMK Muhammadiyah 3 Wates, Apri, Ika and Wahidedi. The focus of this research is to understand the background to reading the Al-Qur'an used as a condition for getting a letter of permission to enter class when you are late for school, to know the punishment for reading the Al-Qur’an come from, and to investigate any concerns among respondents about reading the Al-Qur’an as a punishment. To answer this, researchers used descriptive qualitative methods. The results of the research show that there are indeed rules for reading the Al-Qur’an for students who are late at SMK Muhammadiyah 3 Wates. The research results show that a background in reading the Al-Qur’an is a requirement for obtaining permission to take part in the learning process because students who are late for school have wasted time reading the Al-Qur’an with their classmates. The recommendation to read the Al-Qur’an began when a teacher discovered that his students rarely read the Al-Qur’an, even though each letter in the Qur’an contains ten virtues for those who read it. Apart from that, there are teachers' concerns about their students' treatment of the Qur’an.